Analysis of Weed Diversity, Density and Dominance on Rice Plants in Minahasa, South Minahasa, North Minahasa, and Tomohon Regency - Tirza Selfin Korneles; Orbanus Naharia; Utari Satiman; Marthy Lingkan Stella Taulu; Sukmarayu Pieter Gedoan (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
This study investigates the diversity of weeds in rice plants across Minahasa, South Minahasa, North Minahasa, and Tomohon regency, focusing on the environmental factors influencing the distribution and density of weeds. The research highlights that the diversity of weeds is significantly influenced by environmental factors such as rainfall, soil type, and water management practices applied by farmers. Species such as Marsilea crenata and Panicum disticum dominate areas with poor drainage, while Ludwigia hexandra and Fimbristylis litoralis thrive in fields with better drainage. Observations of weed density at 21 and 42 days after planting revealed that the competition between paddy and weeds changes as the paddy plants mature, with the initial dominance of weeds decreasing as the paddy plants grow stronger. The findings provide valuable insights into weed dynamics and the significant role environmental conditions play in determining their distribution. These results offer guidance for developing more effective and environmentally sustainable weed management strategies. Recommendations include selective herbicide use, mechanical soil cultivation, crop rotation, and improved water management. The study also suggests that further research is needed to assess the impact of climate change on weed diversity and the long-term effectiveness of weed management practices.